1966
DOI: 10.1128/am.14.2.256-260.1966
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pectinolytic Yeasts in the Degradation of Mucilage Layer of Coffea robusta Cherries

Abstract: Pectinolytic yeasts, Saccharomyces marxianus, S. bayanus, S. cerevisiae var. ellipsoideus , and Schizosaccharomyces sp., predominated in the natural fermentation of coffee cherries of Coffea robusta variety grown in Chikmagalur district of Mysore State, India. These yeast species were found on the cherry surfaces, and evidence was adduced to show that the natural fermentation of coffee was the result of activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…Several other bacterial species, including AAB, were also detected at the start of fermentation, but their population generally decreased with fermentation progress. Similar observations were also reported in previous studies (Agate & Bhat, 1966;De Bruyn et al, 2017;Evangelista et al, 2015). Overall, these microbial and pH changes observed in our study are broadly consistent with the findings reported by others, which indicates that microbial fermentation occurred successfully in our laboratory bench-scale study.…”
Section: Isolatessupporting
confidence: 93%
See 1 more Smart Citation
“…Several other bacterial species, including AAB, were also detected at the start of fermentation, but their population generally decreased with fermentation progress. Similar observations were also reported in previous studies (Agate & Bhat, 1966;De Bruyn et al, 2017;Evangelista et al, 2015). Overall, these microbial and pH changes observed in our study are broadly consistent with the findings reported by others, which indicates that microbial fermentation occurred successfully in our laboratory bench-scale study.…”
Section: Isolatessupporting
confidence: 93%
“…Such observations demonstrated the potential impact of yeasts on mucilage degradation compared with bacteria. Several studies reported relatively high pectinolytic activities of yeasts such as Pichia, Candida, and Saccharomyces species during wet coffee fermentation (Agate & Bhat, 1966;Masoud & Jespersen, 2006;de Melo Pereira et al, 2014), which is consistent with our observations.…”
Section: Isolatessupporting
confidence: 92%
“…Schizosaccharomyces pombe was detected in the fermentation of coffee beans in Brazil (Agate and Bhat 1966 ; Silva et al 2000 ). We incubated 18 samples of coffee beans in media MC and YPD and did not detect S. pombe .…”
Section: Discussionmentioning
confidence: 99%
“…from Minas Gerais, Brazil (Evangelista et al, 2015;Silva et al, 2008a,b) and Proteus sp. from Mysore, India (Agate & Bhat, 1966) were isolated from either wet or semidry fermentation processes. On the fungal side, members of Aspergillus, Fusarium, and Penicillium were isolated from Brazil and Colombia (Cruz-O'Byrne et al, 2021;Silva et al, 2000) from wet coffee fermentation.…”
Section: Discussionmentioning
confidence: 99%